Sistemas de governo x responsabilização política:o tratamento jurídico da responsabilidade política nas receitas de governo presidencial e parlamentar - Shirado, Nayana (2009)
The question which arises and is usually revisited at all times and at different latitudes is to choose the best formula to provide the political organization of society, based mainly on the principle of separation of executive, legislative and judicial branches. This study will concentrate the focus of discussion in the steering system of "flexible" separation with mutual dependency between the Executive and the Legislative - parliamentary government and "hard" separation with mutual independence between these two powers, according to the mechanical of checks and balances - presidential government. Thinking of types of systems in a responsible and democratic way, that is, how the organs of power articulate tasks among themselves, is to think of political responsibility as a centerpiece of this mechanism. In this context, the scope of this paper is to point out a domestic and comparative study of political accountability relating parliamentary and presidential governments, against the rule of irresponsibility - "The King can do no wrong" - designed in the tradition of absolutist monarchies. The theoretical horizon outlined here moves through the spectrum from positivist responsibility and access the teleological content of this institute, delimiting the focus of responsibility in the subjective actions of the chief of executive and members of the legislative in our legal system and panoramas of British, Spanish, Italian, French and American governments. Despite the dogmatic contribution of le gal texts, we investigate the philosophical content in the idea of political responsibility, conceived as obligation (activity) and of a perspective of the value (outcome). From this scenario, three methodological precautions were taken to clear our path: the first looked after, within the concept of political responsibility, commitment of staff to respond by an act of political behavior or worthlessness in democratic sphere, the second took care to trace the features of cabinet government in the form of monarchy and republic, with the aim of investigating the tools for measuring the political responsibility of the king, the president of the republic and the prime minister and his cabinet, the third guided by researching in the presidential government the political responsibility of the president and the guarantors of this mechanisms, especially the responsibility of the Chief of Executive and members of Legislative, among us. In conclusion, the study refers to the measurement of political responsibility through a legal vehicle for direct control of political activity - the election - which provides enforcing the trust between elected and electorate, so as that through an act of the will of the citizens the choice of political representatives is made. The study indicates that the number of re-election and the renewal of the seats in parliament act as a thermometer to measure the degree of political accountability to the electorate. Admittedly, however, that the effectiveness of this mechanism requires the existence of a public awareness of the political events and able to influence this process.